Pengaruh Pendidikan Kesehatan Reproduksi Terhadap Peningkatan Pengetahuan Santriwati Putri di Pondok Pesantren Al Mukmin Sukoharjo - Munaaya Fitriyya; Nevia Zulfatunnisa (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
Background: Many life events that will be occurred will not only determine adult life but also the quality of life of the next generation, so this period is a critical one. Maintaining reproductive health is very important, especially for adolescents. Adolescence is the best time to build good hygiene habits, which can be an asset in the long term. Method: This study is pre experimental research with a one-group pre-post test design method using Wilcoxon test. The study population consisted of students at the Al-Mukmin Sukoharjo Islamic boarding school, totally 20 respondents. Results: It can be concluded that the reproductive health education provided has an influence on increasing knowledge, or it can be said that reproductive health education can improve the thinking skills of students. Keywords: Education, reproductive health, adolescence